2019
DOI: 10.1016/j.joto.2019.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Vestibular evoked myogenic potentials in patients with diabetes mellitus

Abstract: Although the exact mechanism and most involved region of the vestibular system have not yet been fully clarified, vestibular dysfunction has been demonstrated in patients with diabetes mellitus (DM). Vestibular evoked myogenic potential (VEMP) is a short latency electromyographic response to sound or vibration stimuli that may reflect otolith organ or related reflex functions. Since its first description in 1992, VEMP has become a significant part of the vestibular test battery as an objective measurement tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Another study [17] found that diabetes causes degeneration and pathological alterations of vestibular type I hair cells in the microvascular end organs of diabetic rats, and hyperglycemia-induced metabolic stress can cause loss of type 1 hair cells in the balloon and cochlear nerve myelinolysis. In addition, vestibulocochlear nerve damage in diabetic rats has been demonstrated, including myelin lamina rupture and myelin thinning.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [17] found that diabetes causes degeneration and pathological alterations of vestibular type I hair cells in the microvascular end organs of diabetic rats, and hyperglycemia-induced metabolic stress can cause loss of type 1 hair cells in the balloon and cochlear nerve myelinolysis. In addition, vestibulocochlear nerve damage in diabetic rats has been demonstrated, including myelin lamina rupture and myelin thinning.…”
Section: Discussionmentioning
confidence: 99%
“…In people older than 60 years, VEMP responses may indicate alterations. 13,14 Therefore, we excluded patients with conductive hearing loss and sensorineural hearing loss, although it is known that sensorineural hearing loss does not affect the results of VEMP. The p13-n23 amplitude differed significantly between the groups in the right ear c-VEMP results.…”
Section: Discussionmentioning
confidence: 99%